Resonance fluorescence of semiconductor quantum dots: Signatures of the electron-phonon interaction - Ahn, K. J.; Förstner, Jens; Knorr, A. (Physical Review B)
Using a fully quantized description of strongly confined electrons interacting with acoustic phonons and the photon field, the nonstationary resonance-fluorescence spectra of a semiconductor quantum dot are investigated. For excitation pulses with durations approaching typical electron-phonon scattering times, the virtual quantum processes yield an observable electron-phonon sideband broadening.
Keywords: tet_topic_qd